Monitoring the hydraulic stability of Antifer blocks : an IoT-based approach - Neiva, Jorge (2022)
Breakwaters are resilient marine infrastructures, or barriers, built out into the sea to protect a coast or a harbour from the force of waves. The environmental conditions that these structures continuously face are challenging and the continuous monitorization of its hydraulic stability is a key success factor for preventive maintenance of these critical infrastructures. This paper introduces the architecture of an IoT solution designed to monitor the hydraulic stability of Antifer blocks, a common building block used for breakwater infrastructures construction, by measuring, recording, processing, and communicating the data related to the displacement of an Antifer block, in a laboratory context. The IoT device has been designed to meet the following requirements: 3D displacement measurement (up to 25 mm); corrosion-proof and waterproof; wireless charging and wireless communication; and autonomy above one month. Preliminary results have shown that the SmartAntifer prototype fulfills the core application requirements and presents an average consumption of 90 mA, which results in 11 hours of autonomy when equipped with a battery with a capacity of 1000 mAh.